Health care reform: Separating insurance from income redistribution - Friedrich Breyer; Andreas Haufler (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Most systems of health care financing in EU member states currently include elements of income redistribution. The paper analyzes the effects of shifting this kind of redistribution to the tax system and argues that this reform could create two types of efficiency gains. On the expenditure side, it would facilitate the adoption of more incentive-compatible insurance contracts, for example through the introduction of copayment schemes. On the revenue side, income redistribution through the general tax system is likely to imply a shadow price of public funds that is lower than if redistribution is carried out through wage-based insurance contributions.
Keywords: H51; I18; 330; health care finance; income redistribution; Gesetzliche Krankenversicherung; Gesundheitsreform; Äquivalenzprinzip; Einkommensverteilung; Gesundheitsfinanzierung; Wohlfahrtseffekt; Theorie